2006
DOI: 10.1002/cncr.21641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of magnetic resonance imaging and positron emission tomography/computed tomography in the presurgical detection of lymph node metastases in patients with uterine cervical carcinoma

Abstract: Ontogenetic samples of endocranial volumes (EVs) from great apes and humans are critical for understanding the evolution of the brain growth pattern in the hominin lineage. However, high quality ontogenetic data are scarce, especially for nonhuman primates. Here, we provide original data derived from an osteological collection of a wild population of Pan troglodytes verus from the Taï Forest National Park, Ivory Coast. This sample is unique, because age, sex, and pedigree information are available for many spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
192
2
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(209 citation statements)
references
References 74 publications
6
192
2
9
Order By: Relevance
“…The specificity of MRI to determine bladder invasion was significantly higher than that of CT (91% vs 73%). A prospective study revealed that Positron Emission Tomography/Computed Tomography (PET/CT) has more sensitivity in detection of lymph node metastasis than MRI (57.6% vs 30.3%) but no statistic difference in specificity (92.6% vs 92.6%) and accuracy (85.1% vs 72.7%) (Choi et al, 2006). In spite of excluding from the FIGO clinical staging investigations, CT or MRI, have clinical benefit in pre-operative assessment of early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of MRI to determine bladder invasion was significantly higher than that of CT (91% vs 73%). A prospective study revealed that Positron Emission Tomography/Computed Tomography (PET/CT) has more sensitivity in detection of lymph node metastasis than MRI (57.6% vs 30.3%) but no statistic difference in specificity (92.6% vs 92.6%) and accuracy (85.1% vs 72.7%) (Choi et al, 2006). In spite of excluding from the FIGO clinical staging investigations, CT or MRI, have clinical benefit in pre-operative assessment of early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cervical cancer with intra-abdominal lesions are inoperative, and cytoreductive surgery does not have an advantage other than lymph node dissection. It is also reported by Choi et al 6 that PET-CT scan has high sensitivity in detecting pelvic lymph node and para-aortic lymph node metastasis. Therefore it is rarely required to expose the upper abdomen.…”
Section: Discussionmentioning
confidence: 66%
“…By providing metabolic imaging information, this technique has demonstrated a high accuracy (85.1%) and specifi city (92.6%) for predicting lymph node involvement [8], confi rming its value in locoregional staging. PET-CT could be used as a tool in the delineation of tumour volumes and the preparation of patient treatment plans, especially when integrated with virtual simulation [9].…”
Section: Concurrent Chemoradiationmentioning
confidence: 85%